2022
DOI: 10.1016/j.ijid.2021.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Endotheliopathy marked by high von Willebrand factor (vWF) antigen in COVID-19 is associated with poor outcome: a systematic review and meta-analysis

Abstract: Background: In this systematic review and meta-analysis, we aimed to compare the level of von Willebrand Factor (vWF) antigen in patients with poor outcome compared to those without. Additionally, we also explored factors that may affect the difference in terms of vWF antigen between the two groups. Methods: A comprehensive literature search was performed using the PubMed, Embase, and Scopus databases from inception up until 7 April 2021. The main outcome was poor outcome, which is a composite of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The finding of lower soluble DPP-IV receptor in COVID-19 in compare to healthy subject might also indicates the role of DPP-IV in facilitating viral entry although the exact interactions between DPP-IV and coronavirus and how it influence the viral entry has not been established [ [59] , [60] , [61] ]. However, since poor glucose control, cytokine storm, and multiorgan dysfunction have been established as a risk factor for worse outcome [ 40 , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ], one might consider the benefit of excellent glucose control, cardiorenal effect and inflammatory modulation of DPP-IV inhibitor as an potential drug in treating T2DM patient with COVID-19 [ 5 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of lower soluble DPP-IV receptor in COVID-19 in compare to healthy subject might also indicates the role of DPP-IV in facilitating viral entry although the exact interactions between DPP-IV and coronavirus and how it influence the viral entry has not been established [ [59] , [60] , [61] ]. However, since poor glucose control, cytokine storm, and multiorgan dysfunction have been established as a risk factor for worse outcome [ 40 , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] ], one might consider the benefit of excellent glucose control, cardiorenal effect and inflammatory modulation of DPP-IV inhibitor as an potential drug in treating T2DM patient with COVID-19 [ 5 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The induction of hypoxia-induced factors and endothelial inflammation during hypoxia and systemic inflammatory response may contribute to the formation of microthrombi [29]. Coagulopathy is one of the hallmarks of COVID-19, there is an alteration in several important parameters of platelet and coagulation function such as von Willebrand factor, d-dimer, and thromboplastin time [34], [35], [39], [42], [43]. Coagulopathy is hypothesized to be one of the most important complications, leading to mortality in patients with COVID-19 [39].…”
Section: Prothrombotic State and Coagulation Disordersmentioning
confidence: 99%
“…In a retrospective cohort study from China, elevated D-dimer was associated with poor prognosis and a higher risk of mortality [28]. Metaanalysis showed that changes in von Willebrand factor level, d-dimer, and thromboplastin time were strongly associated with mortality in patients with COVID-19 [34], [35], [39], [42], [43].…”
Section: Thromboembolism and Coagulation Abnormalitiesmentioning
confidence: 99%
“…Internalization of angiotensin-converting enzyme 2 (ACE2) to increase angiotensin II levels causes vasoconstriction, hyperinflammation, and the release of prothrombotic substances such as von Willebrand factor (VWF), P-selectin, factor VIII, and angiopoietin 2. 17 18 These factors are all involved in the pathogenesis of thrombogenicity in COVID-19. 19 In CAC, bleeding can occur, especially in advanced stages of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%